Preparation method and application of adjustable double-charge polyamide nanofiltration membrane

By adjusting the pH value, salt type and concentration of the polyamine/diamine aqueous solution, combined with the interfacial polymerization technology, an adjustable double-charged polyamide nanofiltration membrane was prepared, which solved the charge and charge of the nanofiltration membrane in the prior art. The problem of difficulty in adjusting physical structures has achieved higher selectivity and application flexibility.

CN119406262AActive Publication Date: 2025-02-11SHANGHAI JINGYU ENVIRONMENT ENG
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411342454.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-02-11
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The prior art is difficult to achieve controllable adjustment of the charge amount and physical structure of the nanofiltration membrane, which makes it difficult to meet the demand for ion retention and selectivity in different application scenarios.

Method used

By adjusting the pH value, salt type and concentration of the polyamine/diamine aqueous solution, combined with the interfacial polymerization technology, an adjustable double-charged polyamide nanofiltration membrane was prepared. This method allows the regulation of the charge, pore size and thickness uniformity of the nanofiltration membrane under different conditions.

Benefits of technology

The controllable adjustment of the charge amount and physical structure of the nanofiltration membrane is achieved, the retention rate of divalent anions and the permeability of monovalent cations is improved, and the selectivity and application flexibility of the nanofiltration membrane are enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of water treatment, and particularly discloses a preparation method and application of an adjustable double-charge polyamide nanofiltration membrane. According to the preparation method of the adjustable double-charge polyamide nanofiltration membrane, a high negative electricity polyamide layer is prepared through a diamine buffer salt / inorganic salt aqueous phase solution and oil phase interfacial polymerization reaction, and a positive electricity polyamide layer is prepared through a polyamine inorganic salt aqueous phase solution and oil phase interfacial polymerization reaction; the charge capacity, the pore diameter, the thickness and the uniformity of the positive electricity layer and the negative electricity layer can be adjusted. The adjustable double-charge polyamide nanofiltration membrane can be applied to the fields of sewage treatment, lithium extraction from salt lakes and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment, and relates to a method for preparing a polyamide composite nanofiltration membrane, in particular to a method for preparing an adjustable double-charged polyamide nanofiltration membrane by using a novel interfacial polymerization. Background Art

[0002] Membrane separation technology is a technology that uses the selectivity of membranes to separate, purify and concentrate characteristic components of raw liquid at the molecular level. Due to its advantages of low energy consumption, good selectivity, environmental friendliness, low operation and maintenance costs and high separation efficiency, it is widely used in seawater desalination, brackish water desalination, sewage treatment, gas separation and organic molecular screening. In the field of membrane separation, nanofiltration membrane technology has attracted much attention due to its excellent selective separation characteristics. Nanofiltration membrane is a separation membrane with a pore size between 0.5 and 2 nm and a molecular weight cutoff of more than 200 Da. At the same time, the membrane surface is usually charged, so it can selectively retain organic matter and high-valent charged ions above 200 Da, and at the same time has selective permeability to low molecular weight organic matter and low-valent ions, and has good selective screening performance.

[0003] The surface charge of the nanofiltration membrane has a decisive influence on its separation performance. Commercial nanofiltration membranes are usually negatively charged, with a high anion retention rate and a low cation retention rate. Therefore, the research and preparation of nanofiltration membranes that can simultaneously retain anions and cations to achieve balanced retention of ions with different charges is the current research focus of nanofiltration membranes. CN202210774026.6 discloses a preparation method and application of a double-charged layer composite membrane generated by an interfacial polymerization reaction, in which a hydrophobic bottom membrane floats in a buffer solution formed by polyphenols and polyamines to obtain a first layer of membrane, and the dried composite membrane is fixed between two reaction containers, and an amine monomer solution and an acyl chloride monomer solution are interfacially polymerized to obtain a second layer of membrane, thereby obtaining a double-charged layer composite membrane with a negative charge on the upper side and a positive charge on the lower side of the selective separation layer. CN202310837733.X discloses a method for preparing amphoteric Janus nanofiltration membrane using a dual-nozzle electrospinning device, wherein the membrane is formed by the reaction of tert-butyl hydroperoxide and 1,3,5-benzenetricarbonyl trichloride to generate a positively charged active layer, and the negatively charged active filter layer is formed by the reaction of tetraethylenepentamine and 1,3,5-benzenetricarbonyl trichloride. Although the prior art can prepare a dual-charge nanofiltration membrane, it cannot achieve controllable regulation of charge quantity. Summary of the invention

[0004] In view of the defects of the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing an adjustable doubly charged polyamide nanofiltration membrane, which can not only prepare a doubly charged nanofiltration membrane, but also adjust the charge and physical structure of the positive layer or negative layer of the doubly charged nanofiltration membrane by adjusting the pH value, salt type and concentration in the polyamine / diamine aqueous solution, thereby achieving controllable regulation of the doubly charged nanofiltration membrane.

[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0006] One aspect of the present invention provides a method for preparing an adjustable dual-charge polyamide nanofiltration membrane, comprising the following steps:

[0007] 1) preparing a diamine buffer salt / inorganic salt phase solution (i.e., the solution contains a buffer salt and / or an inorganic salt), adjusting the salt concentration to 0.005-0.5 M and the pH value to 6-10, to obtain an interfacial polymerization aqueous phase solution;

[0008] 2) using the interfacial polymerization aqueous solution to fully infiltrate the ultrafiltration base membrane for the experiment, and drying it in the air until there is no obvious water stain on the membrane surface, thereby obtaining an ultrafiltration base membrane fully infiltrated with the aqueous solution;

[0009] 3) Mixing polyacyl chloride and organic solvent to prepare polyacyl chloride solution, pouring the polyacyl chloride solution on the surface of ultrafiltration basement membrane, making the polyacyl chloride solution fully contact with aqueous diamine, washing with organic solution after sufficient reaction, and annealing to form a first layer of negatively charged polyamide nanofiltration membrane;

[0010] 4) preparing a polyamine inorganic salt aqueous solution, adjusting the inorganic salt concentration to 0.005-0.5 M and the pH value to 6-10;

[0011] 5) The negatively charged polyamide nanofiltration membrane is fully infiltrated with the polyamine inorganic salt phase solution and dried in the air until there is no obvious water stain on the membrane surface, thereby obtaining a negatively charged bottom membrane fully infiltrated with the aqueous phase solution;

[0012] 6) Mixing polyacyl chloride and organic solvent to prepare polyacyl chloride solution, pouring the polyacyl chloride solution on the surface of the first layer of negatively charged polyamide nanofiltration membrane, allowing the polyacyl chloride solution to fully contact the aqueous phase polyamine monomer, washing with an organic solution after sufficient reaction, to form a second layer of positively charged polyamide nanofiltration membrane;

[0013] 7) The prepared polyamide membrane is annealed to obtain an adjustable double-charged polyamide nanofiltration membrane with a negative lower layer and a positive upper layer.

[0014] Preferably, in step 1), the diamine is selected from at least one of piperazine, ethylenediamine, hexamethylenediamine and thiourea.

[0015] Preferably, in step 1), the buffer salt is selected from at least one of a phosphate buffer system, a carbonate buffer system, a borate buffer system and a citrate buffer system.

[0016] Preferably, in step 1), the inorganic salt is selected from at least one of a chloride system, a sulfate system, a fluoride system, a bromide system, a nitrate system, a silicate system, a tungstate system, a molybdate system, a permanganate system, a sulfate system, a sulfite system and a pyrophosphate system.

[0017] Preferably, the negatively charged nanofiltration membrane in the lower layer of the double-charged polyamide nanofiltration membrane can show the adjustability of negative charge and physical structure according to the changes in the pH value, salt type and concentration of the diamine aqueous phase solution. Among them, the greater the charge of the buffer salt / inorganic salt anion, the higher the negative charge of the prepared nanofiltration membrane, the thinner the membrane thickness, and the larger the pore size; the smaller the pH value, the higher the negative charge of the prepared nanofiltration membrane, the thinner the membrane thickness, and the larger the pore size; the greater the salt concentration, the higher the negative charge of the prepared nanofiltration membrane, the thinner the membrane thickness, and the larger the pore size. In addition, under the conditions of pH value, salt type and concentration specified in the present invention, the prepared negatively charged nanofiltration membrane has good thickness uniformity.

[0018] Preferably, in step 4), the polyamine is selected from at least one of polyallylamine hydrochloride, polydiallyldimethylammonium chloride, polypropylacryloyloxyethyltrimethylammonium chloride, poly-4-vinylpyridine and polyethyleneimine.

[0019] Preferably, in step 4), the inorganic salt in the polyamine inorganic salt aqueous phase solution is selected from at least one of a chloride system, a sulfate system, a fluoride salt system, a bromide salt system, a nitrate system, a silicate system, a tungstate system, a molybdate system, a permanganate system, a sulfate system, a sulfite system and a pyrophosphate system.

[0020] Preferably, the positively charged nanofiltration membrane on the upper layer of the double-charged polyamide nanofiltration membrane can show the adjustability of the positive charge and physical structure according to the changes in the types and concentrations of inorganic salts in the polyamine aqueous phase solution. Among them, the greater the charge of the inorganic salt anion, the lower the positive charge of the prepared nanofiltration membrane, the thinner the membrane thickness, and the larger the pore size; the greater the inorganic salt concentration, the lower the positive charge of the prepared nanofiltration membrane, the thinner the membrane thickness, and the larger the pore size. In addition, under the conditions of the types and concentrations of inorganic salts defined in the present invention, the prepared positively charged nanofiltration membrane has good thickness uniformity.

[0021] Preferably, in steps 3) and 6), the organic solvent is at least one selected from hexane, heptane, pentane, Isopar G, toluene, ethyl acetate and benzene.

[0022] Preferably, in steps 3) and 6), the polyacyl chloride is selected from at least one of 1,3,5-trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride, azelaic acid chloride, adipic acid chloride, and 2,2',4,4'-biphenyltetracarboxylic acid chloride; and the concentration of the polyacyl chloride in the polyacyl chloride solution is 0.25-7.5 mg / mL.

[0023] Preferably, in step 2), the ultrafiltration base membrane material is selected from any one of polysulfone, polyethersulfone, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene nylon, cellulose or cellulose derivatives; and the pore size of the ultrafiltration base membrane is 0.01 to 2 μm.

[0024] Preferably, in steps 3) and 7), the annealing treatment is performed at a temperature of 20 to 80° C. and for a time of 1 to 30 min.

[0025] Preferably, in steps 3) and 6), the diamine / polyamine monomer and the polyacyl chloride are subjected to interfacial polymerization reaction at an interface temperature of 20 to 35° C. and a relative humidity of 50 to 100% for 30 to 90 seconds.

[0026] Another aspect of the present invention provides an adjustable double-charged polyamide nanofiltration membrane prepared by the above-mentioned preparation method. The adjustable double-charged polyamide nanofiltration membrane comprises an ultrafiltration base membrane and a double-layer separation layer formed on the surface of the ultrafiltration base membrane, the upper layer of the double-layer separation layer shows positive charge, the lower layer shows negative charge, and the charge, pore size, uniformity and thickness of the upper and lower polyamide materials are adjustable.

[0027] Another aspect of the present invention provides the use of the adjustable double-charged polyamide nanofiltration membrane in water treatment, and the adjustable double-charged polyamide nanofiltration membrane is applied to sewage treatment, lithium extraction from salt lakes and other fields.

[0028] The above technical solution has at least the following beneficial effects:

[0029] 1. The present invention provides a method for preparing an adjustable double-charged polyamide nanofiltration membrane, through which an adjustable double-charged polyamide nanofiltration membrane can be obtained.

[0030] 2. The present invention combines nanofiltration membrane structure and interfacial polymerization reaction regulation means to prepare a doubly charged polyamide nanofiltration membrane with adjustable positive and negative charges. By adjusting the pH value, salt type and concentration of the polyamine / diamine aqueous solution, the diffusion rate of small molecule amines and the interfacial polymerization reaction rate are designed and optimized. The diffusion rate of small molecule amines is controlled by the electrostatic interaction between anions and small molecule amines, and the interfacial polymerization reaction rate is regulated by the protonation of small molecule amines. The interfacial polymerization reaction can be regulated to a large extent, thereby affecting the physical structure and chemical structure of the nanofiltration membrane, thereby preparing an adjustable doubly charged polyamide nanofiltration membrane.

[0031] 3. The preparation method of the present invention improves the retention rate of divalent anions and reduces the permeability of monovalent cations by regulating the charge of the first layer of negatively charged polyamide nanofiltration membrane, thereby improving the selectivity of the nanofiltration membrane. At the same time, the first layer of loose and highly negatively charged nanofiltration membrane as an intermediate layer provides a good reaction platform for the interfacial polymerization reaction of the second layer of positively charged nanofiltration membrane.

[0032] 4. The preparation method of the present invention solves the problems of the traditional control method being complicated, costly and having unsatisfactory effect. The preparation method is simple, cost-effective, has obvious and stable control effect, is convenient for large-scale preparation, and has strong industrial application value. DETAILED DESCRIPTION

[0033] In order to facilitate the understanding of the present invention, in order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention, and preferred embodiments of the present invention are given. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood. The present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited to the specific embodiments disclosed below.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0035] Although the existing technology can prepare a doubly charged nanofiltration membrane, it cannot achieve controllable regulation of the membrane charge and physical structure. The traditional polyamide nanofiltration membrane is determined by the intrinsic reaction of interfacial polymerization. The interfacial polymerization reaction rate of trimesoyl chloride and small molecule amine at the oil-water interface is very fast, making it difficult to achieve controllable regulation.

[0036] In view of the deficiencies in the prior art, the inventors of this case combined the nanofiltration membrane structure and the means of regulating the interfacial polymerization reaction to prepare a doubly charged polyamide nanofiltration membrane with adjustable positive and negative charges. By adjusting the pH value, salt type and concentration of the polyamine / diamine aqueous solution, the diffusion rate of small molecule amines and the interfacial polymerization reaction rate were designed and optimized. The diffusion rate of small molecule amines was controlled by the electrostatic interaction between anions and small molecule amines, and the interfacial polymerization reaction rate was regulated by the protonation of small molecule amines. The interfacial polymerization reaction can be regulated to a large extent, thereby affecting the physical and chemical structure of the nanofiltration membrane, achieving controllable regulation of the charge, pore size, thickness and thickness uniformity, and preparing an adjustable doubly charged polyamide nanofiltration membrane.

[0037] The present invention constructs a method for preparing an adjustable dual-charge polyamide nanofiltration membrane, wherein a highly negatively charged polyamide layer is prepared by a diamine buffer salt / inorganic salt water phase solution and an oil phase interfacial polymerization reaction, and a positively charged polyamide layer is prepared by a polyamine inorganic salt water phase solution and an oil phase interfacial polymerization reaction, wherein the charge and physical structure of the positive and negative layers can be adjusted, and a high rejection rate is shown for divalent anions and cations. The method for preparing an adjustable dual-charge polyamide nanofiltration membrane comprises the following steps:

[0038] 1) preparing a diamine buffer salt / inorganic salt phase solution, adjusting the salt concentration to 0.005-0.5M and the pH value to 6-10, and obtaining an interfacial polymerization aqueous phase solution; under this pH condition, the negatively charged membrane has high electronegativity, a large degree of looseness (the lower the pH, the larger the pore size), good selectivity, and is conducive to the passage of positive ions with small charge through the membrane, while intercepting positive ions with large charge;

[0039] The diamine is selected from at least one of piperazine, ethylenediamine, hexamethylenediamine and thiourea;

[0040] The buffer salt is selected from at least one of a phosphate buffer system, a carbonate buffer system, a borate buffer system and a citrate buffer system;

[0041] The inorganic salt is selected from at least one of a chloride system, a sulfate system, a fluoride system, a bromide system, a nitrate system, a silicate system, a tungstate system, a molybdate system, a permanganate system, a sulfate system, a sulfite system and a pyrophosphate system.

[0042] 2) using the interfacial polymerization aqueous solution to fully infiltrate the ultrafiltration base membrane for the experiment, and drying it in the air until there is no obvious water stain on the membrane surface, thereby obtaining an ultrafiltration base membrane fully infiltrated with the aqueous solution;

[0043] The ultrafiltration base membrane material is selected from any one of polysulfone, polyethersulfone, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene nylon, cellulose or cellulose derivatives; the pore size of the ultrafiltration base membrane is 0.01-2 μm.

[0044] 3) Mixing polyacyl chloride and organic solvent to prepare polyacyl chloride solution, pouring the polyacyl chloride solution on the surface of ultrafiltration base membrane, making the polyacyl chloride solution fully contact with aqueous diamine, washing with organic solution after sufficient reaction, and forming a first layer of negatively charged polyamide nanofiltration membrane on the front of ultrafiltration base membrane after annealing;

[0045] The organic solvent is selected from at least one of hexane, heptane, pentane, Isopar G, toluene, ethyl acetate and benzene;

[0046] The polybasic acid chloride is selected from at least one of 1,3,5-trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride, azelayl chloride, adipic acid chloride, and 2,2',4,4'-biphenyltetracarboxylic acid chloride;

[0047] The concentration of the polyacyl chloride in the polyacyl chloride solution is 0.25 to 7.5 mg / mL, the temperature of the annealing treatment is 20 to 80° C., and the time is 1 to 30 min;

[0048] The diamine and the polyacyl chloride are subjected to an interfacial polymerization reaction for 30 to 90 seconds at an interface temperature of 20 to 35° C. and a relative humidity of 50 to 100%.

[0049] 4) preparing a polyamine inorganic salt aqueous solution, adjusting the concentration of the inorganic salt solution to 0.005-0.5 M and the pH value to 6-10;

[0050] The polyamine is selected from at least one of polyallylamine hydrochloride, polydiallyldimethylammonium chloride, polypropylacryloyloxyethyltrimethylammonium chloride, poly-4-vinylpyridine and polyethyleneimine.

[0051] 5) The negatively charged polyamide nanofiltration membrane is fully infiltrated with the polyamine inorganic salt phase solution and dried in the air until there is no obvious water stain on the membrane surface, thereby obtaining an ultrafiltration base membrane fully infiltrated with the water phase solution;

[0052] The inorganic salt in the polyamine inorganic salt aqueous solution is selected from at least one of a chloride system, a sulfate system, a fluoride system, a bromide system, a nitrate system, a silicate system, a tungstate system, a molybdate system, a permanganate system, a sulfate system, a sulfite system and a pyrophosphate system.

[0053] 6) Mixing polyacyl chloride and organic solvent to prepare polyacyl chloride solution, pouring the polyacyl chloride solution on the surface of the first layer of negatively charged polyamide nanofiltration membrane, allowing the polyacyl chloride solution to fully contact the aqueous phase polyamine monomer, washing with an organic solution after sufficient reaction, to form a second layer of positively charged polyamide nanofiltration membrane;

[0054] The polyamine monomer and the polyacyl chloride are subjected to an interfacial polymerization reaction for 30 to 90 seconds at an interface temperature of 20 to 35° C. and a relative humidity of 50 to 100%.

[0055] 7) annealing the prepared polyamide membrane to obtain an adjustable double-charged polyamide nanofiltration membrane with a negative lower layer and a positive upper layer;

[0056] The annealing treatment is performed at a temperature of 20 to 80° C. and for a time of 1 to 30 minutes.

[0057] The prepared adjustable double-charged polyamide nanofiltration membrane includes an ultrafiltration base membrane and a double-layer separation layer formed on the surface of the ultrafiltration base membrane. The upper layer of the double-layer separation layer shows positive charge and the lower layer shows negative charge. The charge, pore size, uniformity and thickness of the upper and lower polyamide materials are adjustable.

[0058] The obtained adjustable double-charged polyamide nanofiltration membrane can be applied to sewage treatment, lithium extraction from salt lakes and other fields.

[0059] The following are specific embodiments, including an example of the preparation of an adjustable doubly charged polyamide nanofiltration membrane and a series of examples that demonstrate controllability. It should be noted that when demonstrating controllability, it is difficult to measure the relevant parameters of the positive and negative double-layer membrane, so it is embodied in the form of a single-layer membrane, and its control effect is also applicable to the double-layer membrane.

[0060] Examples 1-4: Demonstration of the controllability of negatively charged polyamide nanofiltration membranes

[0061] Example 1

[0062] After the polysulfone substrate membrane was soaked in a piperazine (2.5 mg / mL) aqueous solution for 120 seconds, it was dried in the air until there was no obvious water stain on the membrane surface, thereby obtaining a polysulfone substrate membrane fully infiltrated with the aqueous phase solution; a 2 mg / ml 1,3,5-benzene trimesoyl chloride hexane solution was poured on the surface of the infiltrated substrate membrane to carry out an interfacial polymerization reaction at a reaction temperature of 25°C and a relative humidity of 80%. After reacting for 60 seconds, the membrane was taken out, washed with n-hexane, and placed in an oven and heated at 60°C for 1 minute to obtain a conventional nanofiltration membrane. TEM showed that the separation layer thickness was 65 nm and the carboxyl density was 0.19 sites·nm at pH 10.5. -3 When the pH value of the test aqueous solution was 7.0, the Zeta potential was -31.0 mV. According to the pore size prediction model, the membrane pore radius was 0.404 nm.

[0063] Example 2

[0064] The pH value of the mixed aqueous solution of piperazine (2.5 mg / mL) and Na3PO4 (0.1 M) was adjusted to 10.0. The polysulfone substrate membrane was soaked in the solution for 120 seconds and then dried in the air until there was no obvious water stain on the membrane surface, thereby obtaining a polysulfone substrate membrane fully infiltrated with the aqueous solution. A 2 mg / ml 1,3,5-benzene trimesoyl chloride hexane solution was poured on the surface of the infiltrated substrate membrane to carry out an interfacial polymerization reaction. The reaction temperature was 25°C and the relative humidity was 80%. After reacting for 60 seconds, the membrane was taken out and washed with n-hexane. The membrane was placed in an oven and heated at 60°C for 1 minute to obtain a negatively charged loose nanofiltration membrane. TEM analysis showed that the surface of the nanofiltration membrane had a relatively smooth structure, the separation layer thickness was 35 nm, and the carboxyl density was 0.36 sites·nm at pH 10.5. -3 When the pH value of the test aqueous solution was 7.0, the Zeta potential was -51.0 mV. According to the pore size prediction model, the membrane pore radius was 0.433 nm.

[0065] Example 3

[0066] The pH value of the mixed aqueous solution of piperazine (2.5 mg / mL) and Na2HPO4 / NaH2PO4 (0.1 M) was adjusted to 9.0. The polysulfone substrate membrane was soaked in the solution for 120 seconds and then dried in the air until there was no obvious water stain on the membrane surface, thereby obtaining a polysulfone substrate membrane fully infiltrated with the aqueous solution. A 2 mg / ml 1,3,5-benzene trimesoyl chloride hexane solution was poured on the surface of the infiltrated substrate membrane to carry out an interfacial polymerization reaction. The reaction temperature was 25°C and the relative humidity was 80%. After reacting for 60 seconds, the membrane was taken out and washed with n-hexane. The membrane was placed in an oven and heated at 60°C for 1 minute to obtain a negatively charged loose nanofiltration membrane. TEM analysis showed that the surface of the nanofiltration membrane had a relatively smooth structure, the separation layer thickness was 28 nm, and the carboxyl density was 0.44 sites·nm at pH 10.5. -3 When the pH value of the test aqueous solution was 7.0, the Zeta potential was -60.5 mV. According to the pore size prediction model, the membrane pore radius was 0.452 nm.

[0067] Example 4

[0068] The pH value of the mixed aqueous solution of piperazine (2.5 mg / mL) and Na2HPO4 / NaH2PO4 (0.1 M) was adjusted to 6.5. The polysulfone substrate membrane was soaked in the solution for 120 seconds and then dried in the air until there was no obvious water stain on the membrane surface, thereby obtaining a polysulfone substrate membrane fully infiltrated with the aqueous solution. A 2 mg / ml 1,3,5-benzene trimesoyl chloride hexane solution was poured on the surface of the infiltrated substrate membrane to carry out an interfacial polymerization reaction. The reaction temperature was 25°C and the relative humidity was 80%. After reacting for 60 seconds, the membrane was taken out and washed with n-hexane. The membrane was placed in an oven and heated at 60°C for 1 minute to obtain a negatively charged loose nanofiltration membrane. TEM analysis showed that the surface of the nanofiltration membrane had a relatively smooth structure, the separation layer thickness was 12 nm, and the carboxyl density was 1.02 sites·nm at pH 10.5. -3 When the pH value of the test aqueous solution was 7.0, the Zeta potential was -68.9 mV. According to the pore size prediction model, the membrane pore radius was 0.496 nm.

[0069] Example 5-7: Demonstration of the controllability of positively charged polyamide nanofiltration membrane

[0070] Example 5

[0071] After the polysulfone substrate membrane was soaked in polyethyleneimine (5.0 mg / mL) solution for 120 seconds, it was dried in the air until there was no obvious water stain on the membrane surface, thereby obtaining a polysulfone substrate membrane fully infiltrated with the aqueous solution; a 2 mg / ml 1,3,5-benzene trimesoyl chloride hexane solution was poured on the surface of the infiltrated substrate membrane to carry out an interfacial polymerization reaction. The reaction temperature was 25°C and the relative humidity was 80%. After reacting for 60 seconds, the membrane was taken out and washed with n-hexane. The membrane was placed in an oven and heated at 60°C for 1 minute to obtain a conventional positively charged nanofiltration membrane. TEM analysis showed that the separation layer thickness was 52 nm. When the pH value of the test aqueous solution was 7.0, the Zeta potential was 35.2 mV. According to the pore size prediction model, the pore radius of the membrane was 0.53 nm.

[0072] Example 6

[0073] NaCl (0.1 M) was added to the aqueous solution of polyethyleneimine (5.0 mg / mL), and the polysulfone substrate membrane was soaked for 120 seconds, and then dried in the air until there was no obvious water stain on the membrane surface, thereby obtaining a polysulfone substrate membrane fully infiltrated with the aqueous solution; a 2 mg / ml 1,3,5-benzene trimesoyl chloride hexane solution was poured on the surface of the infiltrated substrate membrane to carry out an interfacial polymerization reaction. The reaction temperature was 25°C and the relative humidity was 80%. After reacting for 60 seconds, the membrane was taken out and washed with n-hexane. The membrane was placed in an oven and heated at 60°C for 1 minute to obtain a weakly positively charged nanofiltration membrane. TEM analysis showed that the separation layer thickness was 46 nm. When the pH value of the test aqueous solution was 7.0, the Zeta potential was 28.3 mV. According to the pore size prediction model, the pore radius of the membrane was 0.57 nm.

[0074] Example 7

[0075] Na3PO4 (0.1 M) was added to the aqueous solution of polyethyleneimine (5.0 mg / mL), and the polysulfone substrate membrane was soaked for 120 seconds, and then dried in the air until there was no obvious water stain on the membrane surface, thereby obtaining a polysulfone substrate membrane fully infiltrated with the aqueous phase solution; a 2 mg / ml 1,3,5-benzene trimesoyl chloride hexane solution was poured on the surface of the infiltrated substrate membrane to carry out an interfacial polymerization reaction. The reaction temperature was 25°C and the relative humidity was 80%. After reacting for 60 seconds, the membrane was taken out and washed with n-hexane. The membrane was placed in an oven and heated at 60°C for 1 min to obtain a weakly positively charged nanofiltration membrane. TEM analysis showed that the separation layer thickness was 37 nm. When the pH value of the test aqueous solution was 7.0, the Zeta potential was 18.7 mV. According to the pore size prediction model, the pore radius of the membrane was 0.61 nm.

[0076] Example 8: Preparation of adjustable dual-charge polyamide nanofiltration membrane

[0077] In this embodiment, an adjustable double-charged polyamide nanofiltration membrane is prepared, wherein the preparation parameters of the negatively charged loose nanofiltration membrane are the same as those of Example 3, and the preparation parameters of the positively charged nanofiltration membrane are the same as those of Example 7. The specific process is as follows: the pH value of a mixed aqueous solution of piperazine (2.5 mg / mL) and Na2HPO4 / NaH2PO4 (total salt concentration 0.1 M, initial molar ratio of Na2HPO4 to NaH2PO4 is 1:1) is adjusted to 9.0, and the polysulfone substrate membrane is soaked in the solution for 120 seconds, and then dried in the air until there is no obvious water stain on the membrane surface, thereby obtaining a polysulfone substrate membrane fully infiltrated with the aqueous phase solution; a 1,3,5-benzene trimesoyl chloride hexane solution with a concentration of 2 mg / ml is poured on the surface of the infiltrated substrate membrane to perform an interfacial polymerization reaction, the reaction temperature is 25°C, the relative humidity is 80%, and the reaction is carried out for 60 After s, take it out, wash the membrane with n-hexane, place it in an oven, and heat it at 60°C for 1 min to obtain a negatively charged loose nanofiltration membrane; add Na3PO4 (0.1M) to the aqueous solution of polyethyleneimine (5.0 mg / mL), soak the negatively charged loose composite nanofiltration membrane for 120s, and then dry it in the air until there is no obvious water stain on the surface of the membrane, so as to obtain a negatively charged bottom membrane fully infiltrated with the aqueous solution; pour a 1,3,5-benzenetricarbonyl chloride hexane solution with a concentration of 2 mg / ml on the surface of the infiltrated negatively charged bottom membrane to carry out interfacial polymerization reaction, the reaction temperature is 25°C, the relative humidity is 80%, take it out after 60s, wash the membrane with n-hexane, place it in an oven, and heat it at 60°C for 1 min to obtain an adjustable double-charged polyamide nanofiltration membrane with positive charge on the upper layer and negative charge on the lower layer.

[0078] The double-charged nanofiltration membrane prepared in this example was tested with aqueous solution cross-flow at a test temperature of 25°C. It was first refluxed at a pressure of 4 bar for 30 min and then tested at a pressure of 2 bar. The flux was 26.3 L·h -1 ·m -2 bar -1 ; Cross-flow test with 1000ppm Na2SO4 aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 95.1%; cross-flow test with 1000ppm MgSO4 aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 95.7%; cross-flow test with 1000ppm MgCl2 aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 97.2%; cross-flow test with 1000ppm CaCl2 aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 96.1%; cross-flow test with 1000ppm NaCl aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 30.1%; cross-flow test with 1000ppm LiCl aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 35.4%.

[0079] The cross-flow test was carried out on the nanofiltration membrane prepared in Example 3. The test temperature was 25°C. It was first refluxed at 4 bar pressure for 30 min and then tested at 2 bar pressure. The flux was 82.3 L·h -1 ·m -2 bar -1 ; Cross-flow test with 1000ppm Na2SO4 aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 96.1%; cross-flow test with 1000ppm MgSO4 aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 82.7%; cross-flow test with 1000ppm MgCl2 aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 20.3%; cross-flow test with 1000ppm CaCl2 aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 15.2%; cross-flow test with 1000ppm NaCl aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 11.1%; cross-flow test with 1000ppm LiCl aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 15.6%.

[0080] The cross-flow test was carried out on the nanofiltration membrane prepared in Example 7. The test temperature was 25°C. It was first refluxed at 4 bar pressure for 30 min and then tested at 2 bar pressure. The flux was 36.1 L·h -1 ·m -2 bar -1 ; Cross-flow test with 1000ppm Na2SO4 aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 36.1%; cross-flow test with 1000ppm MgSO4 aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 43.5%; cross-flow test with 1000ppm MgCl2 aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 97.3%; cross-flow test with 1000ppm CaCl2 aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 96.9%; cross-flow test with 1000ppm NaCl aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 46.1%; cross-flow test with 1000ppm LiCl aqueous solution, the test temperature is 25℃, the test is under 2bar pressure, the retention rate is 44.6%.

[0081] In summary, we can draw the following conclusions:

[0082] The adjustable double-charged polyamide nanofiltration membrane prepared by the present invention has positive charge on the upper layer and negative charge on the lower layer, and the charge, pore size, uniformity and thickness of the upper and lower polyamide materials are adjustable. The double-charged polyamide nanofiltration membrane shows a high retention rate for Na2SO4, MgSO4, MgCl2 and CaCl2.

Claims

1. A method for preparing an adjustable double-charge polyamide nanofiltration membrane, characterized in that: The steps include: 1) preparing a diamine buffer salt / inorganic salt phase solution, adjusting the salt concentration to 0.005-0.5M and the pH value to 6-10, to obtain an interfacial polymerization aqueous phase solution; 2) using the interfacial polymerization aqueous solution to fully infiltrate the ultrafiltration base membrane for the experiment, and drying it in the air until there is no obvious water stain on the membrane surface, thereby obtaining an ultrafiltration base membrane fully infiltrated with the aqueous solution; 3) Mixing polyacyl chloride and organic solvent to prepare polyacyl chloride solution, pouring the polyacyl chloride solution on the surface of ultrafiltration basement membrane, making the polyacyl chloride solution fully contact with aqueous diamine, washing with organic solution after sufficient reaction, and annealing to form a first layer of negatively charged polyamide nanofiltration membrane; 4) preparing a polyamine inorganic salt aqueous solution, adjusting the inorganic salt concentration to 0.005-0.5 M and the pH value to 6-10; 5) The negatively charged polyamide nanofiltration membrane is fully infiltrated with the polyamine inorganic salt phase solution and dried in the air until there is no obvious water stain on the membrane surface, thereby obtaining a negatively charged bottom membrane fully infiltrated with the aqueous phase solution; 6) Mixing polyacyl chloride and organic solvent to prepare polyacyl chloride solution, pouring the polyacyl chloride solution on the surface of the first layer of negatively charged polyamide nanofiltration membrane, allowing the polyacyl chloride solution to fully contact the aqueous phase polyamine monomer, washing with an organic solution after sufficient reaction, to form a second layer of positively charged polyamide nanofiltration membrane; 7) The prepared polyamide membrane is annealed to obtain an adjustable double-charged polyamide nanofiltration membrane with a negative lower layer and a positive upper layer.

2. The preparation method according to claim 1, characterized in that: In step 1), the diamine is selected from at least one of piperazine, ethylenediamine, hexamethylenediamine and thiourea.

3. The preparation method according to claim 1, characterized in that: In step 1), the buffer salt is selected from at least one of a phosphate buffer system, a carbonate buffer system, a borate buffer system and a citrate buffer system.

4. The preparation method according to claim 1, characterized in that: In step 1), the inorganic salt is selected from at least one of a chloride system, a sulfate system, a fluoride system, a bromide system, a nitrate system, a silicate system, a tungstate system, a molybdate system, a permanganate system, a sulfate system, a sulfite system and a pyrophosphate system.

5. The preparation method according to claim 1, characterized in that: The negatively charged nanofiltration membrane at the lower layer of the double-charged polyamide nanofiltration membrane can show the adjustability of the negative charge amount and physical structure according to the changes in the pH value, salt type and concentration of the diamine aqueous phase solution.

6. The preparation method according to claim 1, characterized in that: In step 4), the polyamine is selected from at least one of polyallylamine hydrochloride, polydiallyldimethylammonium chloride, polypropylacryloyloxyethyltrimethylammonium chloride, poly-4-vinylpyridine and polyethyleneimine.

7. The preparation method according to claim 1, characterized in that: In step 4), the inorganic salt in the polyamine inorganic salt aqueous phase solution is selected from at least one of a chloride system, a sulfate system, a fluoride salt system, a bromide salt system, a nitrate system, a silicate system, a tungstate system, a molybdate system, a permanganate system, a sulfate system, a sulfite system and a pyrophosphate system.

8. The preparation method according to claim 1, characterized in that: The positively charged nanofiltration membrane on the upper layer of the double-charged polyamide nanofiltration membrane can show the adjustability of the positive charge amount and physical structure according to the changes in the types and concentrations of inorganic salts in the polyamine aqueous phase solution.

9. The preparation method according to claim 1, characterized in that: In steps 3) and 6), the organic solvent is at least one selected from hexane, heptane, pentane, Isopar G, toluene, ethyl acetate and benzene.

10. The preparation method according to claim 1, characterized in that: In steps 3) and 6), the polyacyl chloride is selected from at least one of 1,3,5-trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride, azelaic acid chloride, adipic acid chloride, and 2,2',4,4'-biphenyltetracarboxylic acid chloride; and the concentration of the polyacyl chloride in the polyacyl chloride solution is 0.25 to 7.5 mg / mL.

11. The preparation method according to claim 1, characterized in that: In step 2), the ultrafiltration base membrane material is selected from any one of polysulfone, polyethersulfone, polyvinylidene fluoride, polyacrylonitrile, polytetrafluoroethylene nylon, cellulose or cellulose derivatives; the pore size of the ultrafiltration base membrane is 0.01 to 2 μm.

12. The preparation method according to claim 1, characterized in that: In steps 3) and 7), the annealing treatment is carried out at a temperature of 20 to 80°C and for a time of 1 to 30 minutes.

13. The preparation method according to claim 1, characterized in that: In steps 3) and 6), the diamine / polyamine monomer and the polyacid chloride are subjected to interfacial polymerization reaction at an interface temperature of 20 to 35° C. and a relative humidity of 50 to 100% for 30 to 90 seconds.

14. An adjustable double-charge polyamide nanofiltration membrane prepared by any one of the preparation methods of claims 1 to 13, characterized in that: The adjustable double-charged polyamide nanofiltration membrane includes an ultrafiltration base membrane and a double-layer separation layer formed on the surface of the ultrafiltration base membrane. The upper layer of the double-layer separation layer shows positive charge, and the lower layer shows negative charge. The charge, pore size, uniformity and thickness of the upper and lower polyamide materials are adjustable.

15. Use of the adjustable double-charged polyamide nanofiltration membrane as claimed in claim 14 in water treatment, wherein the adjustable double-charged polyamide nanofiltration membrane is applied to sewage treatment and lithium extraction from salt lakes.

Citation Information

Patent Citations

  • A method for preparing a double-charged composite film by interfacial polymerization and its application

    CN115090124B

  • A method for preparing an amphoteric Janus nanofiltration membrane

    CN116764441B

  • Preparation method for generating double-charge-layer composite film through interfacial polymerization reaction and application of double-charge-layer composite film

    CN115090124A

  • High-flux and anti-scaling nanofiltration membrane as well as preparation method and application thereof

    CN116116238A

  • Nanofiltration membrane preparation method and nanofiltration membrane prepared thereby

    WO2023231317A1